Narrative and contemporary poetry - Roberts, Neil (Revista Leitura, 2019)
Contemporary narrative poetry presents a challenge to the teacher: how to approach it from a narratological perspective and still pay attention to the details of poetic language? This essay uses a Bakhtinian approach to explore the generic experiments of five contemporary poets: Tony Harrison, Derek Walcott, Peter Reading, Ted Hughes and Anne Stevenson. DOI: 10.28998/0103-6858.2005v2n36p85-99